2022
DOI: 10.3390/cancers14092049
|View full text |Cite
|
Sign up to set email alerts
|

Front-Line Therapy for Metastatic Renal Cell Carcinoma: A Perspective on the Current Algorithm and Future Directions

Abstract: Over the last decade, the treatment paradigm of metastatic renal cell carcinoma has rapidly evolved, with notable changes in the front-line setting. Combination therapies involving the use of either doublet therapy with immune checkpoint inhibitors or combination VEGFR-directed therapies with immune checkpoint inhibitors have significantly improved clinical outcomes, including prolonged overall survival and durable response to treatment. We aim to highlight the Food and Drug Administration-approved front-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Due to several advantageous characteristics, ICIs play a central role in systemic therapy for aRCC patients, irrespective of risk classi cation or histopathology [13]. In particular, ICI-based combination therapy, consisting of either dual use of ICIs or ICI plus TKI, is regarded as a standard of care, and is widely applied to treatment-naïve aRCC patients [1,7]. However, whether the e cacy of ICI-based combination therapy is modulated by its order of treatment is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to several advantageous characteristics, ICIs play a central role in systemic therapy for aRCC patients, irrespective of risk classi cation or histopathology [13]. In particular, ICI-based combination therapy, consisting of either dual use of ICIs or ICI plus TKI, is regarded as a standard of care, and is widely applied to treatment-naïve aRCC patients [1,7]. However, whether the e cacy of ICI-based combination therapy is modulated by its order of treatment is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ICI was also shown to be effective in aRCC patients previously treated with TKIs [4,5]. In major clinical guidelines, ICI or ICI-based combination regimens are widely recommended as standard systemic therapies against aRCC [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It’s reported that 25% to 30% of RCC patients present with metastatic disease at the time of diagnosis, and one-third of initially cured patients experience systemic progression ( 4 , 5 ). What’s worse, RCC is poorly response to radiotherapy and chemotherapy, the 5-year survival rate of metastatic RCC is only 10% ( 6 , 7 ). With remarkable progress of molecular targeted drug and PD-1/PD-L1 checkpoint blockade immunotherapy, it has significantly improved patients’ prognosis for those with metastatic RCC.…”
Section: Introductionmentioning
confidence: 99%
“…13 The OAAs captured in this assessment (sunitinib, sorafenib, axitinib, everolimus, and pazopanib) represent only five of more than a now dozen approved therapies for this disease. 15 Furthermore, the characterization of systemic therapies was somewhat unclear—the authors appear to designate OAAs and targeted therapies as separate categories, when in principle these are overlapping. Furthermore, some of the systemic therapies identified in the database appear to be overrepresented.…”
mentioning
confidence: 99%
“…It is important to note that between 10% and 17% of patients will achieve a complete response with new targeted therapy/immunotherapy combinations. 15 Thus, clinicians must face the challenge of finding a balance between patients' expectations and clear communication around prognosis. Little is known regarding patient preferences at EOL in this new era of treatment.…”
mentioning
confidence: 99%